Sound source localization by an inverse method using the measured dynamic response of a cylinder. (February 2015) - Djamaa, M.C.; Ouelaa, N.; Pezerat, C.; Guyader, J.L.
Highlights: In this work, an experimental procedure to localize acoustic source is presented. The equation of motion of the structure and the measured velocity at some discrete points are used. The inverse problem is regularized by the choice of an optimum cut-off wavenumber. Numerical simulations from exact and noisy data are presented. Good results are obtained in both numerical and experimental cases. Abstract: This work presents an experimental study to localize an acoustic source inside a cylindrical shell which is applied without contact with the structure. Since this source cannot be detected by direct measurements, the proposed method is based on the measurement of the velocity at some discrete points on the external surface of the shell by a Scanning Laser Vibrometer. The displacements integrated from the measured velocities will be injected into the equation of motion using finite difference schemes. First, some numerical simulations will be presented starting from exact data and then with uncertainties to simulate measurements. Before the regularization process was applied, the distributions resulting from measured velocities cannot be able to locate the acoustic source whenever the measurement uncertainties are present. In this case, a regularization technique based on the filtering of the wavenumber domain which is infected by the noise is applied. The regularization criterion has been applied to the distributions as results of measurements and there the localization of the acoustic source is clearly improved.